2007
DOI: 10.1111/j.1365-2044.2007.05193.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal errors in nitrous oxide delivery

Abstract: SummaryNitrous oxide continues to be used frequently and the possibility of inadvertent fatal hypoxaemia resulting from technical errors with its administration still exists. A Medline analysis revealed only a few case reports over the last 30 years, and a closed claim analysis only reported ‘claims involving oxygen supply lines’ predating 1990. The aim of this study was to assess the frequency of nitrous oxide‐related catastrophes during general anaesthesia in Germany, Austria, and Switzerland. As nitrous oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 31 publications
0
18
0
3
Order By: Relevance
“…Aufgrund fehlender fachwissenschaftlicher Publikationen wurden in einem früheren Artikel Zeitungsarchive zur Detektion tödlicher lachgasbedingter Komplikationen ausgewertet [9]. In ähnlicher Weise diente nun das Internet als Datenquelle.…”
Section: Methodikunclassified
See 1 more Smart Citation
“…Aufgrund fehlender fachwissenschaftlicher Publikationen wurden in einem früheren Artikel Zeitungsarchive zur Detektion tödlicher lachgasbedingter Komplikationen ausgewertet [9]. In ähnlicher Weise diente nun das Internet als Datenquelle.…”
Section: Methodikunclassified
“…Während die lachgasbedingten Todesfäl-le in der Laienpresse teils heftig diskutiert wurden ( [4]), erschienen sie offensichtlich in keinem der entsprechenden medizinischen Fachjournale [9]. Ein Fehlen dieser Komplikationen in den bestehenden Fehlermeldesystemen kann aber auch nicht sonderlich überraschen, wenn man die Grundlage dieser "Critical-incident"-Reportsysteme" (CIRS) bedenkt.…”
Section: Externe Aufarbeitungunclassified
“…[78] Misconnection of O 2 pipeline hose to N 2 O cylinder in the manifold room by technical personnel has resulted in hypoxic gas delivery. [910] Insertion of the Equanox (50% each of O 2 and N 2 O) probe accidentally into the N 2 O wall outlet resulted in 100% N 2 O delivery. [11] These problems were compounded by either lack of oxygen analyser or failure to recognise the hypoxia early and changing over to an alternate plan by the concerned anaesthesiologist.…”
Section: Hazards Of Anaesthesia Machinesmentioning
confidence: 99%
“…Gilmour et al [12] reported a case of oxygen supply contamination with trichloroeth ane, originated from the fluid used to clean the hose that connected the [13][14][15][16]. Gilmour et al [12] reported a case of oxygen supply contamination with trichloroeth ane, originated from the fluid used to clean the hose that connected the [13][14][15][16].…”
Section: 5 Nitric Oxide and Nitrogen Dioxide Concentration In Gas Ormentioning
confidence: 99%